A mediating role for anticipated regret in predicting retirement savings intention between groups with (without) past behaviour. (29th July 2014) - Croy, Gerry; Gerrans, Paul; Speelman, Craig P.
Abstract A recent global trend has been the shifting of responsibility for retirement income planning from the public purse to individuals, with an associated encouragement to contribute more to retirement savings. This research investigated the influence of anticipated regret on the intention to make extra voluntary retirement savings. Results revealed that anticipated regret plays a powerful affective role in the formation of behavioural intention by conveying the influence of attitude and subjective norm to intention. Implications of the results with respect to possible interventions relating to behaviour change are considered.